2021
DOI: 10.4239/wjd.v12.i8.1220
|View full text |Cite
|
Sign up to set email alerts
|

Place of intravitreal dexamethasone implant in the treatment armamentarium of diabetic macular edema

Abstract: Diabetic macular edema (DME) is a very important and well-known cause of visual loss in diabetics. Blood–retina barrier disruption and consequent intraretinal fluid accumulation may lead to retinal thickening at the posterior pole namely DME. Even though it is not clearly understood, current evidence suggests that chronic low-grade inflammation characterized with various cytokines has a major role in the occurrence of DME. Clinical trials are continuously shaping our treatment approaches for the eyes with DME.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…The sustained dexamethasone intravitreal implant (DEX implant; Ozurdex), a biodegradable device, was first approved by the Food and Drug Administration in 2009 for the treatment of ME with RVO. Its unique dosage form can overcome the ocular administration barrier and prolong the action time of dexamethasone in the eye [11,16] . In previous studies, both the aflibercept and dexamethasone implant have been shown to be effective in the treatment of ME [17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…The sustained dexamethasone intravitreal implant (DEX implant; Ozurdex), a biodegradable device, was first approved by the Food and Drug Administration in 2009 for the treatment of ME with RVO. Its unique dosage form can overcome the ocular administration barrier and prolong the action time of dexamethasone in the eye [11,16] . In previous studies, both the aflibercept and dexamethasone implant have been shown to be effective in the treatment of ME [17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies report that especially the presence of intraretinal hyperreflective dots and serous macular detachment is associated with inflammation and intravitreal corticosteroid injections are beneficial in improving these findings [17]. However, intravitreal steroid injections are not generally preferred as firstline therapy because they accelerate the development of glaucoma and cataracts [18]. Dexamethasone implant is the only corticosteroid licensed for DME treatment in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the e cacy and safety of TA in the treatment of post-operative CME [17]- [21]. The most recent method of treatment used is the intravitreal dexamethasone implant (IDI) which is a biodegradable copolymer that has an extended release for 6 months, with peak response at 60 days [22].…”
Section: Introductionmentioning
confidence: 99%